2022
DOI: 10.1016/j.sjbs.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of SARS-CoV-2 RNA-dependent RNA polymerase inhibitors from the major phytochemicals of Nigella sativa: An in silico approach

Abstract: The coronavirus disease 2019 (COVID-19), which emerged in December 2019, continues to be a serious health concern worldwide. There is an urgent need to develop effective drugs and vaccines to control the spread of this disease. In the current study, the main phytochemical compounds of Nigella sativa were screened for their binding affinity for the active site of the RNA-dependent RNA polymerase (RdRp) enzyme of the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). The binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The initial siRNA structure (sequence: UGC-GCU-ACG-AUC-GACGAU-G) was obtained using the nucleic acid builder (NAB) included in AMBER18 [24], with RNA.OL3 forcefield [25,26]. PEI starting structure was built using Discovery Studio Visualizer [27], with protonation state assigned based on recent NMR studies [28] for neutral pH and assigned uniformly.…”
Section: Molecular Dynamics Calculationsmentioning
confidence: 99%
“…The initial siRNA structure (sequence: UGC-GCU-ACG-AUC-GACGAU-G) was obtained using the nucleic acid builder (NAB) included in AMBER18 [24], with RNA.OL3 forcefield [25,26]. PEI starting structure was built using Discovery Studio Visualizer [27], with protonation state assigned based on recent NMR studies [28] for neutral pH and assigned uniformly.…”
Section: Molecular Dynamics Calculationsmentioning
confidence: 99%
“…Black cumin increases the amount of breast milk due to the combination of lipid elements and the structure of hormones (Mehlsen et al, 2022). Furthermore, the content of polyphenols in black cumin, which is also discovered in katuk leaves, plays a significant role in increasing prolactin levels (Mir et al, 2022). Black cumin administration was examined in mice, with increases in milk production by 31.1% and 37.6% compared to the control group that was not provided with black cumin (Walsh et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these enzymes represent some emerging drug-targets against which no confirmed drug is presently available [15][16][17]. Although several in silico studies have reported the possible inhibitory potential of various N. sativa phytochemicals against SARS-Cov-2 [26][27][28][29][30][31][32], the anti-mycobacterial potential of N. sativa constituents has been reported in a few studies only [12][13][14]. In this preliminary study, the nine prominent phytochemical compounds of N. sativa were selected and their inhibitory potential against the three selected mycobacterial enzymes was investigated through in silico molecular docking.…”
Section: Discussionmentioning
confidence: 99%